Bundled postconditioning therapies improve hemodynamics and neurologic recovery after 17 min of untreated cardiac arrest. (February 2015) - Bartos, Jason A.; Matsuura, Timothy R.; Sarraf, Mohammad; Youngquist, Scott T.; McKnite, Scott H.; Rees, Jennifer N.; Sloper, Daniel T.; Bates, Frank S.; Segal, Nicolas; Debaty, Guillaume; Lurie, Keith G.; Neumar, Robert W.; et al.
Abstract: Objective: Ischemic postconditioning (stutter CPR) and sevoflurane have been shown to mitigate the effects of reperfusion injury in cardiac tissue after 15 min of ventricular fibrillation (VF) cardiac arrest. Poloxamer 188 (P188) has also proven beneficial to neuronal and cardiac tissue during reperfusion injury in human and animal models. We hypothesized that the use of stutter CPR, sevoflurane, and P188 combined with standard advanced life support would improve post-resuscitation cardiac and neurologic function after prolonged VF arrest. Methods: Following 17 min of untreated VF, 20 pigs were randomized to Control treatment with active compression/decompression (ACD) CPR and impedance threshold device (ITD) ( n = 8) or Bundle therapy with stutter ACD CPR + ITD + sevoflurane + P188 ( n = 12). Epinephrine and post-resuscitation hypothermia were given in both groups per standard protocol. Animals that achieved return of spontaneous circulation (ROSC) were evaluated with echocardiography, biomarkers, and a blinded neurologic assessment with a cerebral performance category score. Results: Bundle therapy improved hemodynamics during resuscitation, reduced need for epinephrine and repeated defibrillation, reduced biomarkers of cardiac injury and end-organ dysfunction, and increased left ventricular ejection fraction compared to Controls. Bundle therapy also improved rates of ROSC (100% vs. 50%), freedom from major adverse events (50% vs. 0% at 48 h), and neurologic function (42% with mild or no neurologic deficit and 17% achieving normal function at 48 h). Conclusions: Bundle therapy with a combination of stutter ACD CPR, ITD, sevoflurane, and P188 improved cardiac and neurologic function after 17 min of untreated cardiac arrest in pigs. All studies were performed with approval from the Institutional Animal Care Committee of the Minneapolis Medical Research Foundation (protocol #12-11).